Identification of low energy nuclear recoils in a gas time projection chamber with optical readout. (1st December 2020) - Baracchini, E; Benussi, L; Bianco, S; Capoccia, C; Caponero, M; Cavoto, G; Cortez, A; Costa, I A; Di Marco, E; D'Imperio, G; Dho, G; Iacoangeli, F; et al.
Abstract: The search for a novel technology, which is able to detect and reconstruct nuclear recoil events in the keV energy range, has become increasingly important now that vast regions of high mass weakly-interacting-massive-particle–like dark matter candidates have been excluded. Gaseous time projection chambers (TPC) with optical readout are very promising candidates combining the complete event information provided by the TPC technique with the high sensitivity and granularity of the latest generation light sensors. A TPC with an amplification at the anode, obtained with gas electron multipliers (GEMs), was tested at the Laboratori Nazionali di Frascati. Photons and neutrons from radioactive sources were employed to induce recoiling nuclei and electrons with kinetic energy in the range 1–100 keV. A He-CF4 (60/40) gas mixture was used at atmospheric pressure and the light produced during the multiplication in the GEM channels was acquired by a high-position resolution and low-noise complementary metal - oxide semiconductor camera and a photomultiplier. A multi-stage pattern recognition algorithm based on an advanced clustering technique is presented here. A number of cluster-shaped observables are used to identify nuclear recoils induced by neutrons, which originated from a AmBe source against x-ray 55 Fe photoelectrons. An efficiency of 18% to detect nuclear recoils with an energy of about 6 keV is reached, while suppressing 96% of the 55 Fe photoelectrons, making this optical read-out gas TPC a very promising candidate for future investigations of ultra-rare events such as directional direct dark matter searches.